Digital Literacy in Islamic Elementary Education: The Role of Teachers in Strengthening Student Competencies - Sukmawati, Sukmawati; Muthmainna, Muthi'ah; Harmiati, Harmiati; Safira, Shalsa (State Islamic Institute of Palopo, 2025)
The rapid development of digital technologies has reshaped learning environments and highlighted the urgent need for digital literacy competencies among primary school students, including those in Islamic educational settings. This study aims to analyze the multifaceted roles of teachers in strengthening digital literacy in Islamic primary schools, focusing on how teachers facilitate technology use, guide ethical digital behavior, innovate curriculum design, and motivate learners. Employing a descriptive qualitative approach through a systematic literature review, this research synthesizes findings from national and international journal articles published within the last decade. The results reveal four dominant teacher roles that consistently appear across the literature. First, teachers act as facilitators by utilizing digital platforms and resources to support student-centered learning and foster independent exploration. Second, they serve as guides for digital ethics, helping young learners navigate issues such as online safety, credibility of information, privacy, and responsible digital communication. Third, teachers function as curriculum innovators by integrating digital tools and project-based learning tasks that enhance critical thinking, creativity, and engagement. Fourth, teachers act as motivators, providing emotional support and creating positive digital learning experiences that build students’ confidence in using technology. These findings indicate that digital literacy development requires a holistic pedagogical approach that integrates technological skills, ethical reasoning, and affective support. The study contributes to the existing body of knowledge by situating digital literacy within the moral-pedagogical context of Islamic education, highlighting the importance of harmonizing technological competence with Islamic values. The implications suggest the need for capacity building, continuous professional development, and supportive digital infrastructure to enable teachers to perform these roles effectively. Overall, this research reinforces the central role of teachers in shaping digitally competent and ethically grounded learners in the era of educational digital transformation.